Evaluation of the relationship between the expression of AgNOR and Ki67 with the recurrence rate in central granulomatous giant cell lesions: A case‐control - Mina T. B. Dareh; Azadeh Andisheh‐Tadbir; Arezoo Aghakouchakzadeh (Wiley, 2024)
Abstract Objectives Giant cell granuloma is a local nonneoplastic lesion that is divided into two categories, based on its site of occurrence: Central and peripheral giant cell granuloma. Central giant cell granuloma is an intraosseous lesion that has a tendency to recure even in surgically treated cases. Several studies have proven that there is an association between different lesions clinical behavior and their histological features. The aim of this study was to evaluate the expression of AgNOR and Ki67 in lesions with and without recurrency. Material and Methods Files and records of 35 patients who had been histologically diagnosed with central giant cell granuloma were investigated. Histological features were studied after performing AgNOR staining and Ki67 marker. The data were analyzed by chi‐square, Fisher, and T‐test. Results Acquired data indicated that the count of AgNOR staining and Ki67 marker was significantly higher in lesions with recurrency than the lesions with no recurrency. The same results were attained from Ki67 intensity. Conclusion The current study indicated that AgNOR staining and Ki67 marker have prognostic value in predicting recurrency of central giant cell granuloma lesions.